Mechanism of fuel mixing of hydrogen multi-jet in presence of upstream convergent/divergent ramp at supersonic flow. (8th June 2022) - Wang, Fuzhang; Majdi, Hasan Sh.; Dhahad, Hayder A.; Nofal, Taher A.; Musa, Awad
Abstract: The enactment of the fuel mixing structure is crucial for the advance of supersonic vehicles. All-inclusive efforts have been done to disclose the impacts of different parameters on instrument of the fuel combination with air within the combustion chamber. In the present work, comprehensive computational investigations have been done to explore the importance of oblique ramp upstream on the fuel mixing process of hydrogen multi-jets at supersonic cross airflow. The primary attention of the current study is to compare the role of interaction of air and fuel by the existence of an oblique ramp upstream of four cross jets. Flow analysis is also done to unveil the main difference of convergent and divergence ramps located upstream of each injector. For simulation of the proposed models, Computational Fluid Dynamics (CFD) is employed to resolve RANS equations with the SST turbulence model in high-speed free stream. The main significant factors i.e. mixing efficiency and circulation factor are also compared in our work for comparison of the flow parameters and mixing concepts. According to our investigations, the presence of the upstream oblique jet meaningfully enhances the fuel mixing as flow moves downstream of injectors. The outcomes also showed that productivity of the divergent ramp is higher than that of the convergent one due to high jet diffusion in the depth of the domain by the creation of a strong horseshoe vortex. Highlights: Impacts of inclined ramp in upstream of multi-jets at supersonic cross flow is studied. Influence of convergent and divergent ramp on mixing performance is entirely investigated. RANS equation are solved with SST turbulence model for the simulation of the supersonic cross flow. Impacts of divergent ramp on fuel mixing is more than convergent one.